Association of IL12A Expression Quantitative Trait Loci (eQTL) With Primary Biliary Cirrhosis in a Chinese Han Population. Issue 19 (May 2016) - Li, Ping; Lu, Guanting; Cui, Ying; Wu, Ziyan; Chen, Si; Li, Jing; Wen, Xiaoting; Zhang, Haoze; Mu, Shijie; Zhang, Fengchun; Li, Yongzhe
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Genome-wide association studies in European individuals have revealed that IL12A is strongly associated with primary biliary cirrhosis (PBC). However, this association was not detected in replicative studies conducted in Chinese Han and Japanese populations. To verify contributions of genetic variants of IL12A to the pathogenesis of PBC in Chinese populations, a replicative study of 22 single nucleotide polymorphisms (SNPs) around the IL12A gene locus was performed in a cohort of 586 PBC cases and 726 healthy controls. Three out of the 22 SNPs were significantly associated with PBC. The 2 SNPs with the most significant association signal were rs4679868 ( P  = 6.59E−05, odds ratio [OR] = 1.554 [1.253–1.927]) and rs6441286 ( P  = 8.00E−05, OR = 1.551 [1.250–1.924]). These 2 SNPs were strongly linked to each other (r 2  = 0.981), and both were found to be significantly associated with PBC in European populations. An expression quantitative trait loci (eQTL) analysis was performed based on the observation that these 2 SNPs were located in proximity to 2 enhancers verified by luciferase reporter systems in the HEK293 cell line. The results of eQTL analysis, conducted using the publically accessible data, showed that the risk alleles of rs4679868 and rs6441286 were significantly associated with decreased expression of IL12A in lymphoblastoid cell lines derived from individuals of Chinese Han ancestry ( P  = 0.0031 for rs4679868 and P  = 0.0073 for rs6441286). In addition, the risk alleles of the 2 SNPs were significantly associated with down-regulation of SCHIP1, a celiac disease susceptible gene, 91.5 kb upstream of IL12A . These results not only demonstrated that IL12A is associated with PBC in the Chinese Han population but also identified a potential mechanism for its involvement in the pathogenesis of PBC.